Inclusive Global Value Chains : Policy Options for Small and Medium Enterprises and Low-Income Countries - Cusolito, Ana Paula; Safadi, Raed; Taglioni, Daria (Washington, DC: World Bank, 2016)
This report's focus is making global value chains (GVCs) more inclusive. To achieve inclusiveness is by overcoming participation constraints for Small and Medium Enterprises (SMEs) and facilitation access for Low Income Developing Countries (LIDCs). The underlying assumption is that most firms in LIDCs are SMEs. Even larger firms in LIDCs are likely to face similar challenges to SMEs, including a less supportive domestic operating environment and weaker institutions that lead to higher fixed costs and challenges to compete on the international markets. The two major points of this report are (1) participation in GVCs is heterogeneous and uneven, across and within countries, and (2) available data and survey-based evidence suggest that SMEs’ participation in GVCs is mostly taking place through indirect contribution to exports, rather than through exporting directly. The report makes the case that policy action, at the national and multilateral level, can make a difference in achieving more inclusive GVCs through: a holistic approach to reform spanning trade, investment, and domestic policies countries and investments in expanding the statistical base and analysis of GVCs and in sharing knowledge on best practices on enabling policies and programs. The report elaborates on three broad areas of recommendations: (1) establishing a trade and investment action plan for inclusiveness defining clear and achievable objectives on trade and investment policy and identifying the necessary complementary domestic policy actions; (2) complementing trade, investment, and domestic policy actions by providing the needed political leadership and support to enhance collaboration across the sectors, and establishing global platforms for sharing best practices; and (3) providing political support for the establishment of a multi-year plan to expand and upgrade the statistical foundation necessary to increase the capacity of all countries to identify and implement policies that can contribute to stronger, more inclusive and sustainable growth and development, globally.